Therapy compliance and fixed-dose combinations in arterial hypertension treatment. Focus on a fixed-dose combination of felodipine and metoprolol - S. A. Shalnova (Кардиоваскулярная терапия и профилактика, 2009)
The paper discusses fixed-dose combined therapy of arterial hypertension (AH), as an effective method for increasing AH treatment compliance.